EFEKTIVITAS PROSES PEMBELAJARAN GAMBAR TEKNIK SISWA KELAS X TEKNIK BANGUNAN SMK NEGERI 1 BATIPUH - 2183-2187, Winda Yuhelsi (CIVED, 2018)
Abstract—. This study includes the research of case study which purposes to know the situation or the factual data. The population is all students of SMK N 1 Batipuh, consisting of several competence skills, namely : the wood construction engineering, the architecture engineering, the audio video engineering, the light vehicles engineering, the mechanical engineering, the engineering of electric power installation, and the motorcycle engineering. The samples were determined 43 students of the population by using simple random sampling. The research instrument used questionnaire. The data was analyzed, using Microsoft Excel program and the. The result shows that 1) for the attitude indicator, the attitude of the students in the learning process of the Technical Drawing is still low, 2) for the indicators of the ability to understand the lesson, the ability of the students to understand the Technical Drawing lesson, 3) for persistence indicator, student persistence in process less technical lesson 4) for opportunity indicators, most students have not been able to take advantage of opportunities, and 5) for quality teaching indicators, quality teaching that can be applied in school environment is still minimal. In general, it can be concluded that the learning process of Technical Student Drawing Class X Building Technique at SMK Negeri 1 Batipuh still less effective.  Keywords: Effectiveness, Technical Drawing